Infection of lymphocytes by a virus that aborts cytotoxic T lymphocyte activity and establishes persistent infection. - Borrow, P; Tishon, A; Oldstone, M (1991)
For viruses to establish persistent infections in their hosts, they must possess some mechanism for evading clearance by the immune system. When inoculated into adult immunocompetent mice, wild-type lymphocytic choriomeningitis virus (LCMV ARM) induces a CD8(+)-mediated cytotoxic T lymphocyte (CTL) response that clears the infection within 7-14 d (CTL+ [P-]). By contrast, variant viruses isolated from lymphoid tissues of persistently infected mice fail to induce a CTL response and are thus able to establish a persistent infection in adult mice (CTL- [P+]). This report compares the interaction of CTL+ (P-) and CTL- (P+) viruses with cells of the immune system. Both types of virus initially bind to 2-4% of CD4+ and CD8+ T lymphocytes and replicate within cells of both subsets. The replication of CTL- (P+) and CTL+ (P-) viruses in lymphocytes in vivo is similar for the first 5 d after initiating infection. Thereafter, in mice infected with CTL- (P+) variants, lymphocytes retain viral genetic information, and infectious virus can be recovered throughout the animals' lives. In contrast, when adult mice are infected with wild-type CTL+ (P-) LCMV ARM, virus is not recovered from lymphocytes for greater than 7 d after infection. A CD8(+)-mediated anti-LCMV CTL response is induced in such mice. Clearance of infected lymphocytes is produced by these LCMV-specific CTLs, as shown by their ability to lyse lymphocytes expressing LCMV determinants in vitro and the fact that depletion of CD8+ lymphocytes before infection with CTL+ (P-) viruses results in levels of infected lymphocytes similar to those found in undepleted CTL- (P+)-infected mice. Hence, CTL-mediated lysis of T lymphocytes carrying infectious virus is a critical factor determining whether virus persists or the infection is terminated.